Kemampuan Menulis Arab Melayu Mahasiswa Laki-laki Program Studi Pendidikan Bahasa dan Sastra Indonesia Angkatan 2022–2023 FKIP Universitas Riau - Arief Ersyandi; Muhammad Farhan; Febi Aidilla; Hasnah Faizah AR (BADAN PENERBIT STIEPARI PRESS, 2024)
Research to find out how Malay Arabic writing skills are in male students of the Indonesian Language and Literature Education study program in the class of 2022-2023, Faculty of Teacher Training and Education, Riau University. Writing using Malay Arabic script is a cultural lesson, especially for the Malay community. Malay Arabic is used to communicate about culture and customs in written form. Writing is one of the language skills that must be possessed. Writing is an activity that expresses ideas in written form. The research method used is quantitative by giving a writing test with 10 questions to male students class 2022-2023. The test was carried out to test the ability to write in Malay Arabic, for the highest frequency with a score of 90, there were 2 students with a percentage of 9.52% and the lowest was with scores of 50 and 60 which had a percentage of 4.76% and 19.05%. So it was concluded that male students from the class of 2022-2023 were capable of writing Malay Arabic because they got a score of 70-90 reaching 76.19%.